2015
DOI: 10.1073/pnas.1506763112
|View full text |Cite
|
Sign up to set email alerts
|

Optimized tools for multicolor stochastic labeling reveal diverse stereotyped cell arrangements in the fly visual system

Abstract: We describe the development and application of methods for high-throughput neuroanatomy in Drosophila using light microscopy. These tools enable efficient multicolor stochastic labeling of neurons at both low and high densities. Expression of multiple membrane-targeted and distinct epitope-tagged proteins is controlled both by a transcriptional driver and by stochastic, recombinase-mediated excision of transcription-terminating cassettes. This MultiColor FlpOut (MCFO) approach can be used to reveal cell shapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
691
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 522 publications
(738 citation statements)
references
References 45 publications
13
691
0
Order By: Relevance
“…Previous studies that examined 331 auditory responses in Dsx+ neurons (Zhou et al, 2015;2014) did not resolve which subtype 332 carried the response. Using a stochastic labeling approach (Nern et al, 2015), we confirmed 333 that only five out of eight Dsx+ cell types in the female brain project to the LJ (Kimura et al, 334 2015): pC1, pC2l/m, pMN1, and pMN2, but not pCd1/2 and aDN ( Fig. 4A and Fig.…”
Section: Dsx+ Pc2l Neurons Are Pulse Song Detectors 328mentioning
confidence: 57%
“…Previous studies that examined 331 auditory responses in Dsx+ neurons (Zhou et al, 2015;2014) did not resolve which subtype 332 carried the response. Using a stochastic labeling approach (Nern et al, 2015), we confirmed 333 that only five out of eight Dsx+ cell types in the female brain project to the LJ (Kimura et al, 334 2015): pC1, pC2l/m, pMN1, and pMN2, but not pCd1/2 and aDN ( Fig. 4A and Fig.…”
Section: Dsx+ Pc2l Neurons Are Pulse Song Detectors 328mentioning
confidence: 57%
“…We investigated the details of the global NPF-GAL4 expression pattern further using stochastic labeling with the Multi Color FlipOut technique (ref. 31 and Fig. S8).…”
Section: Significancementioning
confidence: 96%
“…First, are large-scale efforts to identify and target individual neurons in specific brain regions rather than identifying neurons using the above described behavioral screening methods. For example, spGAL4 combinations have been identified that express in the different neurons innervating the fly mushroom body (Aso et al 2014a) and visual system (Tuthill et al 2013;Nern et al 2015). The activity of each neuron type was then systematically manipulated to assess their contributions to different behaviors (Tuthill et al 2013;Aso et al 2014b).…”
Section: Complementary Approachesmentioning
confidence: 99%